Reduced hip bone mineral density is related to physical fitness and leg lean mass in ambulatory individuals with chronic stroke - Pang, Marco YC (2005)
Following a stroke, reduced level of physical activity and functional use of the paretic leg may lead to bone loss and muscle atrophy. These factors and the high incidence of falls may contribute to hip fractures in the stroke population. This study was the first to examine total proximal femur bone mineral content (BMC) and bone mineral density (BMD) and their relationship to stroke-specific impairments in ambulatory individuals with chronic stroke (onset >1 year). We utilized dual-energy X-ray absorptiometry (DXA) to acquire proximal femur and total body scans on 58 (23 women) community-dwelling individuals with chronic stroke. We report total proximal femur BMC (g) and BMD (g/cm(2)) derived from the proximal femur scans, and lean mass (g) and fat mass (g) for each leg derived from the total body scans. Each subject was evaluated for ambulatory capacity (Six Minute Walk Test), knee extension strength (hand-held dynamometry), physical fitness [Maximal oxygen uptake (VO(2)max)], and spasticity (Modified Ashworth Scale). Results showed that the paretic leg had significantly lower proximal femur BMD, lean mass, and percent lean mass but higher fat mass than the non-paretic leg for both men and women. Proximal femur BMD of the paretic leg was significantly related to ambulatory capacity (r=0.33, p=0.011), muscle strength (r=0.39, p=0.002), physical fitness (r=0.57, p<0.001) but not related to spasticity (r=−0.23, p=0.080). Multiple regression analysis showed that lean mass in the paretic leg was a major predictor (R(2)=0.371, p<0.001) of the paretic proximal femur BMD. VO(2)max was a significant predictor of both paretic proximal femur BMD (R(2)=0.325, p<0.001) and lean mass in the paretic leg (R(2)=0.700, p<0.001). Further study is required to determine whether increasing physical fitness and lean mass is important to improve hip bone health in chronic stroke.